ChemInform Abstract: Iridium‐Catalyzed Asymmetric Hydrogenation of 2‐Pyridyl Cyclic Imines: A Highly Enantioselective Approach to Nicotine Derivatives. Issue 27 (18th June 2015) - Guo, Cui; Sun, Dong‐Wei; Yang, Shuang; Mao, Shen‐Jie; Xu, Xiao‐Hua; Zhu, Shou‐Fei; Zhou, Qi‐Lin
Abstract A substituent adjacent to the pyridine N atom is crucial to block the coordination ability of the pyridine moiety, an effect which is evidently overturned by the proximate second N atom in substrate (Vb).